Control social de la coca: Lecciones del Trópico de Cochabamba (Bolivia) para Colombia - Beatriz Ramos; Jean Paul Benavides; María Alejandra Vélez; Gilda Jauregui; David Restrepo (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2023)
– Within the framework of the global prohibitionist policy, the Bolivian State has stood out for challenging orthodoxy and calling for innovative policies in defense of the coca leaf and the rights of the coca-growing population. In particular, the Cato Agreement that was opened between the Bolivian State and the cocaleros in 2004 to authorize legal family plots for coca cultivation and the social control system for its monitoring is highlighted. Based on secondary information and interviews carried out in the Cochabamba Tropics with members of unions and other relevant actors, it is found that the main effects of this system are the reduction of conflicts and violent confrontations, the reduction of human rights violations by part of the public forces and the consensual rationalization of coca crops. Although this system of social control of coca stands out for deviating from the traditional strategies of substitution and eradication, it has some limitations in its scope: there has been little industrialization of the coca leaf for the alternative market, the control of the Coca leaf supply has been moderate -although Bolivia has been the country that has maintained the most stable number of hectares in the Andean region- and some peasant associations have been affected by the limited number of plots authorized for legal cultivation. However, the Bolivian experience with the social control of coca leaves several replicable lessons for the countries of the Andean region because it has traced a path towards the decriminalization of productive activities with the coca leaf. This document prepares lessons for Colombia based on the social control system to reduce conflict, promote peace in the coca-growing territories and, identify, generate legitimacy in the coca-growing activity. Drug policy in Bolivia has allowed the legalization of coca growing areas and could well suspect how a transition mechanism regulates the coca economy.
Keywords: K38; 330; Coca; Bolivia; Colombia; anti-drug policies; drugs